Copernicus and the Aristotelian tradition : education, reading, and philosophy in Copernicus's path to heliocentrism - Goddu, André, 1945- (Brill, 2010)
Taking into account the most important results of the scholarly literature since 1973 and the best Polish scholarship of the past century, this is the first comprehensive study of Copernicus's achievement in English that examines Copernicus's path to heliocentrism from the perspective of late medieval philosophy, the Renaissance recovery of ancient literature and science, and early-modern editions of books that Copernicus used. The principal goals are to explain his commitment to the existence of celestial spheres, and the logical foundations for his views about hypotheses. In doing so, the wo.
Keywords: Copernicus, Nicolaus, -- 1473-1543 -- Knowledge and learning.; Copernicus, Nicolaus, -- 1473-1543 -- Sources.; Copernicus, Nicolaus, -- 1473-1543; Kopernikus, Nikolaus.; Astronomy -- History -- 16th century.; Cosmology -- History -- 16th century.; Science -- History -- 16th century.; Philosophy, Medieval.; Astronomie -- Histoire -- 16e siècle.; Cosmologie -- Histoire -- 16e siècle.; Sciences -- Histoire -- 16e siècle.; Philosophie médiévale.; SCIENCE -- Astronomy.; Astronomy; Cosmology; Learning and scholarship; Philosophy, Medieval; Science; Heliozentrisches System; Astronomie; Wissenschaftsentwicklung; 1500-1599; Geschichte 1490-1600.; History; Sources